2007
DOI: 10.4161/cbt.6.6.4241
|View full text |Cite
|
Sign up to set email alerts
|

The RUNX2 transcription factor cooperates with the YES-associated protein, YAP65, to promote cell transformation

Abstract: The Runt box domain DNA-binding transcription factors (RUNX) play key roles in hematopoietic, bone, and gastric development. These factors regulate angiogenesis and tumorigenic events, functioning as either activators or repressors of target genes. Although RUNX2 is an essential bone maturation factor, it has also been found to promote transformation in vivo and cell proliferation in vitro, perhaps by associating with specific coactivators or corepressors. Adenoviral-mediated overexpression of dominant negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…Similarly, the overexpression of YAP in mammary epithelial cells elicits transformation, perhaps because YAP collaborates in these cells with the amplified myc (51). Simple overexpression of YAP in certain epithelial or fibroblastic cells (HEK293, NIH3T3) does not cause oncogenic transformation, unless additional genes are co-expressed or amplified (32,52). The presence of overexpressed c-myc in systems where YAP caused transformation suggested that for YAP to be oncogenic requires the expression of an additional gene that encodes the anti-apoptotic protein (such as c-Myc, cyclin E, or Runx2).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the overexpression of YAP in mammary epithelial cells elicits transformation, perhaps because YAP collaborates in these cells with the amplified myc (51). Simple overexpression of YAP in certain epithelial or fibroblastic cells (HEK293, NIH3T3) does not cause oncogenic transformation, unless additional genes are co-expressed or amplified (32,52). The presence of overexpressed c-myc in systems where YAP caused transformation suggested that for YAP to be oncogenic requires the expression of an additional gene that encodes the anti-apoptotic protein (such as c-Myc, cyclin E, or Runx2).…”
Section: Discussionmentioning
confidence: 99%
“…20 YAP tyrosine phosphorylation, putatively by Src family kinases, also enables YAP binding to Runx2, resulting in suppression of Runx2 transcriptional activity toward p21 cdki 21 while promoting transformation. 22 Thus, YAP is capable of being regulated by diverse upstream inputs that appear to elicit distinct and even opposing outputs, e.g., as an oncogene 23 or a tumor suppressor. 24 What then are YAP's physiologic functions in various contexts; what are the relevant upstream inputs, and by what mechanisms are each of these functions regulated?…”
Section: Yap Is An Oncogene That Is Frequently Overexpressed In Commomentioning
confidence: 99%
“…Importantly, YAP, a mediator of Hippo signaling, interacts with the native RUNX2 protein and suppresses RUNX2 transcriptional activity in a dose-dependent manner. Inhibition of the Yes kinase dissociates endogenous Runx2-YAP complexes (22)(23)(24). Moreover, the RUNX2 transcription factor cooperates with YAP65 to promote oncogenic transformation (25).…”
Section: ---Imentioning
confidence: 99%